2016
DOI: 10.1039/c5dt03754a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of metastable β-Ag2WO4: an experimental and theoretical approach

Abstract: Metastable silver tungstate (β-Ag2WO4) has attracted much attention lately because of its many potential applications. However, the synthesis of metastable phases of inorganic compounds is challenging because of the ease of transformation to the stable phase. We have overcome this challenge and have successfully synthesized β-Ag2WO4 microcrystals using a dropwise precipitation (DP) method in aqueous media at low temperature. The microcrystals were characterized by X-ray diffraction (XRD), including powder X-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 46 publications
5
23
1
Order By: Relevance
“…This emission peak in the blue region is typically related to distorted [WO 6 ] octahedral in the aand b-Ag 2 WO 4 crystals. 9,15,35,45 However, in our samples, it can be related to distorted [WO 4 ] tetrahedral. For the a-Ag 2 WO 4 phase, another diffused emission in the red region, from 620 to 640 nm, can be attributed to the [AgO y ] clusters.…”
Section: Pl Spectramentioning
confidence: 64%
See 1 more Smart Citation
“…This emission peak in the blue region is typically related to distorted [WO 6 ] octahedral in the aand b-Ag 2 WO 4 crystals. 9,15,35,45 However, in our samples, it can be related to distorted [WO 4 ] tetrahedral. For the a-Ag 2 WO 4 phase, another diffused emission in the red region, from 620 to 640 nm, can be attributed to the [AgO y ] clusters.…”
Section: Pl Spectramentioning
confidence: 64%
“…For example, a metastable b-Ag 2 WO 4 phase, which coexisted with a weak amount of a-phase, was obtained using a co-precipitation method at pH 4; 31 in addition, the synthesis of pure b-Ag 2 WO 4 at low temperatures has also been reported. 30 Recently, our research group reported the synthesis of b-Ag 2 WO 4 microcrystals by simple 34 and drop-wise precipitation 35 methods. Moreover, Gupta et al presented a new strategy for synthesizing hexagonal metastable b-Ag 2 WO 4 at room temperature through the use of aliovalent Eu 3+ dopants (to induced the orthorhombic (a-Ag 2 WO 4 ) to hexagonal (b-Ag 2 WO 4 ) phase transition) along with the coprecipitation method.…”
Section: Introductionmentioning
confidence: 99%
“…Orthorhombic is the most stable, and its chemical stability is retained up to ~347 ºC, while β-and γ-Ag 2 WO 4 are metastable, being easily transformed to α-Ag 2 WO 4 under heating at 187°C and 257 ºC, respectively 30 . Regardless of the crystallographic phase, the lattice crystal of Ag 2 WO 4 comprises a system of building-block units formed by a series of allotropic forms of [WO 6 ] and [AgO y ] clusters 15,[22][23][24]29 Since the physical and chemical properties are heavily dependent on structural features, those properties of each Ag 2 WO 4 structure will depend on the order-disorder relationship between these clusters, since a symmetry break induced by strain, stress, and distortions within the Ag 2 WO 4 crystal lattice may create new and distinct structures, and thereby give rise to new and different properties 15,23,33 . According to the published literature, these structural variations are a consequence of the synthesis method and experimental conditions (temperature, processing time, solvent, heating source, pH, template, electron beam exposure, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…According to the published literature, these structural variations are a consequence of the synthesis method and experimental conditions (temperature, processing time, solvent, heating source, pH, template, electron beam exposure, etc.) 10,11,16,29,33 . The preparation of α-Ag 2 WO 4 has been successfully carried out by several methods which include solid state reaction [34][35][36] , co-precipitation 22,37-39 , laser ablation in liquid (LAL) 18 , hydrothermal 19,[21][22][23][24][25][26][27]29,[40][41][42] , sonochemical 22,28 and microemulsion 22 methods.…”
Section: Introductionmentioning
confidence: 99%
“…Our research group investigates Ag-containing semiconductors that have attracted significant attention owing to their rich history in technical applications, e.g., in catalysis, 44 photocatalysis, 45 for gas sensors, 46 and antimicrobial agents. 45 In this context, a variety of Ag-containing oxides such as Ag 2 WO 4 in their different polymorph forms a-Ag 2 WO 4 , 20 b-Ag 2 WO 4 , 21,47 and g-Ag 2 WO 4 48 have been studied. Various Ag-based compounds such as b-Ag 2 MoO 4 , 49 Ag 3 PO 4 , 50,51 b-AgVO 3 , 52 and Ag 2 CrO 4 53 have shown the ability to form Ag NPs under electron beam irradiation.…”
Section: Introductionmentioning
confidence: 99%